2017
DOI: 10.3390/genes8040120
|View full text |Cite
|
Sign up to set email alerts
|

MYC, Cell Competition, and Cell Death in Cancer: The Inseparable Triad

Abstract: Deregulation of MYC family proteins in cancer is associated with a global reprogramming of gene expression, ultimately promoting glycolytic pathways, cell growth, and proliferation. It is well known that MYC upregulation triggers cell-autonomous apoptosis in normal tissues, while frankly malignant cells develop resistance to apoptotic stimuli, partly resulting from MYC addiction. As well as inducing cell-autonomous apoptosis, MYC upregulation is able to trigger non cell-autonomous apoptotic death through an ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 106 publications
(151 reference statements)
0
23
1
Order By: Relevance
“…First, we analyzed the expression of two canonical Wnt/β‐catenin target genes, involved in cancer cell proliferation and survival that are activated by nuclear translocation of β‐catenin: C‐MYC and BIRC5. BIRC5 encodes the protein survivin (Di Giacomo, Sollazzo, Paglia, & Grifoni, ; Verdecia et al, ). We treated T‐ALL cell lines for 24 hr with ICG‐001, ZSTK‐474, or the combination of the two drugs and we evaluated the expression of the two genes by qRT‐PCR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we analyzed the expression of two canonical Wnt/β‐catenin target genes, involved in cancer cell proliferation and survival that are activated by nuclear translocation of β‐catenin: C‐MYC and BIRC5. BIRC5 encodes the protein survivin (Di Giacomo, Sollazzo, Paglia, & Grifoni, ; Verdecia et al, ). We treated T‐ALL cell lines for 24 hr with ICG‐001, ZSTK‐474, or the combination of the two drugs and we evaluated the expression of the two genes by qRT‐PCR.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, our findings demonstrated that ICG-001 and ZSTK-474 have cytostatic effects when administrated separately while they induce apoptosis when administrated together.3.2 | Wnt/β-catenin and PI3K/Akt/mTOR signaling pathway are modulated by ICG-001 and ZSTK-474To understand how ICG-001 and ZSTK-474 act at the molecular level, we analyzed the expression of some components of Wnt/β-catenin(Figure 3a,b) and PI3K/Akt signaling at the transcript and/or protein level.First, we analyzed the expression of two canonical Wnt/β-catenin target genes, involved in cancer cell proliferation and survival that are activated by nuclear translocation of β-catenin: C-MYC and BIRC5. BIRC5 encodes the protein survivin (DiGiacomo, Sollazzo, Paglia, & Grifoni, 2017;Verdecia et al, 2000). We treated T-ALL cell lines for 24 hr with ICG-001, ZSTK-474, or the combination of the…”
mentioning
confidence: 99%
“…The abnormal activation of this pathway initiates the expression disorder of downstream target genes such as c-Myc and cyclin D1. c-Myc protein has the dual function of stimulating cell proliferation and regulating apoptosis (Ciribilli et al 2015;Di Giacomo et al 2017). Increased β-catenin in cytoplasm activates cyclin D1 which is key regulators of cell cycle promoting cell division, leading to uncontrolled cell proliferation and carcinogenesis (Mo et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that, in malignant cells, the expression of the MYC oncogene is crucial for cancer cells to colonise organs at the expense of less performant neighbours. As a consequence of this, a functional MYC gene is necessary for the survival and clonal expansion of tumorous masses [36][37][38] .…”
Section: Cancer Cells Are Dependent On Mapk Pathway Genes For Their Smentioning
confidence: 99%